Perceptions, approaches, and needs of Czech GPs in the management of patients with persistent somatic symptoms: the results of a nationwide cross-sectional survey - Seifert, Martin; Sebela, Antonin; Olde Hartman, Tim (BMC primary care, 2025)
BACKGROUND: General practitioners (GPs) perceive patients with persistent somatic symptoms (PSS) as frustrating and difficult to manage. Patients commonly express dissatisfaction with the care they receive and often feel stigmatised and not taken seriously. Some Czech GPs use the option of extra psychosomatic education which focuses on better understanding and management of patients with PSS. OBJECTIVES: To explore perceptions of Czech GPs, with and without additional psychosomatic training, regarding the care of patients with PSS, their beliefs, approaches in the management, and their organisational and educational needs. METHODS: A nationwide cross-sectional survey study among Czech GPs exploring experiences, perceptions, and needs in managing patients with PSS was conducted. Statistical and qualitative approaches were performed to analyse the data. RESULTS: A total of 152 GPs (37 with and 115 without additional psychosomatic training) participated in this survey (response rate 20,3%). GPs struggle with negative emotions, communication with patients, diagnostic uncertainty, patients' lack of understanding, the workload these patients generate, lack of specialized care, and other problems of the healthcare system. They call for more psychosomatic education and communication training. This should include theoretical explanatory models, Balint groups, and other kinds of supervision or peer groups. GPs with additional psychosomatic training feel more confident and competent caring for these patients, compared to GPs without such additional training (OR = 4.1; 95% CI = 1.85-9.11); p < 0.005). Furthermore, they view PSS patients as less burdensome (OR = 4.69; 2.11-10.4; p < 0.001). CONCLUSIONS: GPs struggle with caring for patients with PSS. GPs with additional psychosomatic education indicate that they have more confidence and competence. Czech GPs call for more time and reimbursement when caring for patients with PSS, more psychosomatic training, better availability of specialized psychosomatic care, and better interdisciplinary cooperation.
Keywords: lidé; Middle Aged; Adult; vztahy mezi lékařem a pacientem; General Practitioners; Medically Unexplained Symptoms; Female; průzkumy a dotazníky; postoj zdravotnického personálu; Humans; Physician-Patient Relations; průřezové studie; Cross-Sectional Studies; Česká republika; lidé středního věku; mužské pohlaví; Czech Republic; ženské pohlaví; pacienti bez organického nálezu; Male; praktičtí lékaři; dospělí; Surveys and Questionnaires; Attitude of Health Personnel